Spatial distribution of iron and aluminum in pore water and bottom sludge of the meromictic acid lake no 54, Łuk Mużakowski, Poland = Zawartość żelaza i glinu w wodzie porowej i osadach dennych acidotroficznego zbiornika meromiktycznego nr 54 w Łuku Mużakowskim, Polska - Jachimko, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The spatial distribution of iron and aluminum in bottom sludge and pore water of the meromictic acid pit lake no 54 situated in Łuk Mużakowski, Poland were examined. Samples were taken three times from two places located within the meromictic zone and one out of it. Chemical composition of pore water and sludge in vertical profiles were analysed
Keywords: osady denne; woda porowa; zbiornik meromiktyczny; Łuk Mużakowa; bottom sludge; pore water; meromixis